2003
DOI: 10.1590/s0021-75572003000100014
|View full text |Cite
|
Sign up to set email alerts
|

Fatores prognósticos e sobrevida em recém-nascidos com hérnia diafragmática congênita

Abstract: ResumoObjetivo: analisar a importância de fatores prognósticos para sobrevida, no período neonatal, de pacientes com hérnia diafragmática congênita (HDC) tratados no Hospital das Clínicas da FMUSP e comparar os resultados com os da literatura. Com isso, permitir a atualização do aconselhamento familiar e orientar mudanças de conduta em nosso serviço.Método: estudo retrospectivo de 27 casos consecutivos de recém-nascidos com HDC, admitidos no serviço de cirurgia pediátrica do Instituto da Criança do HCFMUSP ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This possibility is supported when the neonatal mortality of 88% in our series is considered in the context of the 40% mortality reported in a previous study published by pediatric surgeons from our hospital; in that study, CDH was diagnosed postnatally. 25 Additionally, Harrison et al 17 recently demonstrated that adequate and specialized neonatal care can improve neonatal survival to about 70% in cases with prenatally diagnosed isolated CDH, even in those cases without prenatal treatment. This finding means that each hospital may have different neonatal mortality rates based on the prenatal selection of population, prenatal interventions, degree of specialization of neonatal care group, and type of postnatal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is supported when the neonatal mortality of 88% in our series is considered in the context of the 40% mortality reported in a previous study published by pediatric surgeons from our hospital; in that study, CDH was diagnosed postnatally. 25 Additionally, Harrison et al 17 recently demonstrated that adequate and specialized neonatal care can improve neonatal survival to about 70% in cases with prenatally diagnosed isolated CDH, even in those cases without prenatal treatment. This finding means that each hospital may have different neonatal mortality rates based on the prenatal selection of population, prenatal interventions, degree of specialization of neonatal care group, and type of postnatal treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 17 18 Second, identification of risk factors can help in patient counselling. 19 If certain procedures are deemed to have a high risk of readmission within a specific period, healthcare providers can inform patients and their families during the preoperative period. Lastly, by being able to pinpoint high-risk paediatric patients, healthcare providers transition from reactive responses to proactive measures.…”
Section: Introductionmentioning
confidence: 99%